THE ANALYSIS OF PANDAN LEAF (Pandanus amaryllifolius Roxb) EXTRACT AS INHIBITOR ON CORROSION RATE OF STAINLESS STEEL ORTHODONTIC WIRE - Herawani Herawani; Diana Wibowo; Fajar Kusuma Dwi Kurniawan (Dentino : Jurnal Kedokteran Gigi, 2018)
Background: Corrosion is a physical phenomenon that occurs due to electrochemical reactions between the metal and its environment which can lead to decreased quality of the metal so it becomes rough, fragile and easily wrecked. The cause of corrosion is the release of ion that occur due to the interaction of the wire to the environment with acid pH and friction between one component with other components. Purpose: This research aims to analyze pandan leaf extract as an inhibitor in reducing the corrosion rate of stainless steel wire. Methods: This type of research includes true experimental design with post test only control group design. The subject of this research consisted of three group: one control group and two treatment groups. The stainless steel wire control group was immersed in a saline solution, the stainless steel wire treatment group was immersed in the extract of 600 ppm and 1000 ppm pandan leaf. Each group consisted of 10 samples of scratched stainless steel wire along the wire, which is was cut 5 cm long and immersed in a solution od saline along with the extract of pandan. Results: The results showed that the average rate of corrosion of stainless steel wire immersed in the extract of 1000 ppm pandanleaf is was equal to 2,70419x10-5 mm/y, the average rate of corrosion of stainless steel wire immersed in the extract of 600 ppm pandan leaf was equal to 6,77152x10-5 mm/y and the average rate of corrosion of stainless steel wire immersed in a solution of saline was equal to 1,26262x10-5 mm/y. Conclusion: Based on the results of the research, it can be concluded that the corrosion rate of orthodontic stainless steel wire immersed in the extract of 1000 ppm pandan leaf is lower than the extract of 600 ppm pandan leaf.